The Impact of Political Factors on State Fragility and the Growth of Extremism in West Africa: A Case Study of the Sahel Region (Mali, Burkina Faso, and Niger) - reza khorasani; hamid Alizadeh lisar (رهیافتهای سیاسی و بین المللی)
Introduction: State fragility in African countries is a critical and pressing issue, particularly in the Sahel and West Africa region. Countries such as Mali, Burkina Faso, and Niger have become emblematic of fragile states due to a combination of internal challenges and the influence of regional and international intervening powers. This fragility has created conditions conducive to the growth and expansion of extremist organizations like ISIS and Al-Qaeda. One significant contributor to state fragility is political instability. Over the past four years (2020–2024), these three West African countries have experienced recurrent political crises. Key political indicators of fragility include weakened government legitimacy, failure to provide public services, violations of human rights, and the erosion of the rule of law. Additionally, the West African region has been a hotspot for terrorist activity. The operations of Al-Qaeda and ISIS affiliates in the Sahel countries have steadily expanded, undermining the stability of governments in this region. Many Sahel governments struggle to effectively control their territories, with some being classified as "failed states." Political crises in the region are further exacerbated by ethnic and cultural pluralism, weak national identity, failures in nation-building, and disputes over the distribution of resources and justice. The emergence of weak and fragile states in West Africa has triggered crises that extend beyond their borders, affecting neighboring countries and adjacent regions. A central issue in fragile states is the crisis of authority, which is closely tied to ethnic, tribal, and religious divides. These divisions often fuel coups and intensify the activities of extremist group. This research seeks to explore the relationship between key political indicators of state fragility and the growth of terrorism. Its aim is to establish or refute the existence of a link between these phenomena.Method: The study employs a descriptive-analytical approach, relying on library resources and the conceptual framework of state fragility to analyze the subject.Results and discussion: The findings reveal that governments in West African countries, particularly Mali, Burkina Faso, and Niger, lack the capacity to ensure security and stability within their societies. These governments are plagued by political crises, including diminished legitimacy, inadequate public services, human rights violations, and weak adherence to the rule of law. Extremist groups, such as affiliates of Al-Qaeda and ISIS, as well as separatist movements, have exploited the political vacuum created by fragile states in the region. These groups have expanded their activities, leveraging the lack of effective governance to ensure their survival and growth.Conclusion: Governments in this region are continuously confronted with the threat of political instability. The activities of fundamentalist movements are among the most significant factors contributing to political crises and the fragility of governments in this area. Analyzing the state-building crisis, particularly in the Sahel region of Africa, reveals that the failure of state-building and the inability to transition from governmental fragility are linked to four key factors: persistent disputes over power, intense struggles for political dominance, loss of trust in political leadership, and the subsequent breakdown of the political socialization process.